Implementation Of Work Stress In Moderating Work-Life Balance And Flexible Work Arrangements For Job Satisfaction During The Covid-19 Pandemic - Butarbutar, Marisi; Kurnia Lubis, Abdi; Tua Siregar, Robert; Supitriyani, Supitriyani (Publisher Cv. Inara, 2022)
Teachers as human resources in schools have demands that the implementation and work-life balance and flexible work arrangement can be balanced and minimize work stress. The implementation of online learning systems that can make teachers do work-life balance and flexible work arrangements should be able to reduce stress and increase job satisfaction. But the reality in the field is that many teachers do not get job satisfaction. The purpose of this study was to analyze the description and effect of work-life balance, flexible work arrangement, job satisfaction and job stress. The object of this research is the State Senior High School PNS Teachers in Pematang Siantar City who have been certified as many as 168 people. Data analysis techniques used are normality test, regression analysis, correlation coefficient and determination and hypothesis testing. The test was carried out using the SPSS Statistic version 20 program. The results showed are Jjb satisfaction, work-life balance, flexible work arrangement and work stress were in the answers with the criteria of agree/satisfied. The practice of flexible work arrangements affects work-life balance. The results of the regression have a positive influence between each variable. The results of the correlation coefficient analysis obtained a strong and positive relationship. The results of hypothesis testing show a positive and significant effect. Work stress variable is not a moderating variable. It is concluded that the application of work-life balance and flexible work arrangements can increase job satisfaction and work stress is a debilitating variable.